(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Pressure ulcers are a major patient safety concern in critical care settings, contributing to prolonged hospitalization, increased healthcare costs, and avoidable complications. Nurses play a vital role in preventing pressure ulcers; however, their effectiveness depends on adequate knowledge, a positive attitude, and the ability to overcome organizational barriers. Limited local evidence exists in Pakistan, particularly in Peshawar, regarding nurses’ knowledge, attitudes, and perceived barriers toward pressure ulcer prevention. Objectives: This study aimed to assess (1) the level of knowledge of critical care nurses regarding pressure ulcer prevention, (2) their attitudes toward preventive practices, and (3) the perceived barriers that hinder effective pressure ulcer prevention in critical care units. Material and Methods: A quantitative descriptive cross-sectional study was conducted among 123 critical care nurses working in ICU, CCU, MICU, SICU, and CICU units across three hospitals in Peshawar: Rehman Medical Institute, Northwest General Hospital, and Hayatabad Medical Complex. Data were collected using three standardized tools: the Pressure Ulcer Knowledge Assessment Tool (PUKAT 2.0), the Attitude toward Pressure Ulcer Prevention (APuP) scale, and a validated Barriers Assessment Questionnaire. Descriptive statistics were analyzed using SPSS version 27. Results: Participants (n = 123) were mostly men (69; 56.1%), and the majority held a BSN degree (96; 78.0%). Most nurses were between 20–29 years old (87; 70.7%) and had 6 months to 1 year of experience in the critical care unit (55; 44.7%). Critical care nurses were found to have poor knowledge regarding pressure ulcer prevention (77; 62.6%), while only a small proportion demonstrated good knowledge (24; 19.5%). Despite this, the majority of nurses showed a positive attitude toward pressure ulcer prevention (114; 92.7%). In terms of perceived barriers, nurses reported multiple challenges, with the most common being heavy workload and inadequate staffing, lack of standardized guidelines, and shortage of essential equipment. Overall, nurses expressed the presence of several significant barriers to effective pressure ulcer prevention. Findings indicate a clear disconnect between nurses’ highly positive attitudes and their limited knowledge levels. The presence of substantial organizational barriers further suggests that even motivated nurses may struggle to implement evidence-based preventive practices consistently. Conclusion: The study highlights a substantial gap between nurses’ highly positive attitudes and their insufficient knowledge of pressure ulcer prevention. Organizational barriers—including staffing shortages, limited resources, and lack of standardized guidelines—further hinder effective prevention practices. Strengthening training programs, improving resource availability, and implementing standardized clinical protocols are essential to enhance pressure ulcer prevention in critical care settings.